Epilepsy, dissociative seizures, and mixed: Associations with time to video-EEG. (March 2021) - Kerr, Wesley T.; Zhang, Xingruo; Hill, Chloe E.; Janio, Emily A.; Chau, Andrea M.; Braesch, Chelsea T.; Le, Justine M.; Hori, Jessica M.; Patel, Akash B.; Allas, Corinne H.; Karimi, Amir H.; Dubey, Ishita; et al.
Highlights: There are delays to video-electroencephalographic monitoring for seizures. Access to healthcare through employment or school shortens delays. Ictal behavior suggestive of limbic epilepsy had longer delays. Some factors associated with dissociative seizures had shorter delays. Abstract: Purpose: Video-electroencephalographic monitoring (VEM) is a core component to the diagnosis and evaluation of epilepsy and dissociative seizures (DS)—also known as functional or psychogenic seizures—but VEM evaluation often occurs later than recommended. To understand why delays occur, we compared how patient-reported clinical factors were associated with time from first seizure to VEM (TVEM) in patients with epilepsy, DS or mixed. Methods: We acquired data from 1245 consecutive patients with epilepsy, VEM-documented DS or mixed epilepsy and DS. We used multivariate log-normal regression with recursive feature elimination (RFE) to evaluate which of 76 clinical factors interacting with patients' diagnoses were associated with TVEM. Results: The mean and median TVEM were 14.6 years and 10 years, respectively (IQR 3–23 years). In the multivariate RFE model, the factors associated with longer TVEM in all patients included unemployment and not student status, more antiseizure medications (current and past), concussion, and ictal behavior suggestive of temporal lobe epilepsy. Average TVEM was shorter for DS than epilepsy, particularly for patients with depression, anxiety, migraines, and eye closure. Average TVEM was longer specifically for patients with DS taking more medications, more seizure types, non-metastatic cancer, and with other psychiatric comorbidities. Conclusions: In all patients with seizures, trials of numerous antiseizure medications, unemployment and non-student status was associated with longer TVEM. These associations highlight a disconnect between International League Against Epilepsy practice parameters and observed referral patterns in epilepsy. In patients with dissociative seizures, some but not all factors classically associated with DS reduced TVEM.